ANALISIS SISTEM PEMBERIAN UPAH DALAM MENINGKATKAN PRODUKTIVITAS KERJA KARYAWAN DITINJAU DARI PERSPEKTIF EKONOMI ISLAM: STUDI KASUS DI PERKEBUNAN PT GLENMORE BANYUWANGI - Nurul Hidayah (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2022)
This study aims to explain the system applied in wages plantation pt glenmore employees in improving work productivity, explained the system to increase work productivity for plantation workers in Perkebunan PT Glenmore. This research adopting descriptive qualitative. In the process of collecting the data using several methods, that is a method of observation, interviews and documentation. Data analysis technique using analysis qualitative data, data (reduction presentation of data, triangulation data, and withdrawals conclusion or verify). But the research we can conclude that the system for plantation in pt glenmore has been running well based on the suggestion of the government and in accordance with the agreement. The wages plantation in PT Glenmore have also qualified for the islamic in perspective. Wages that would improve employees wages labor productivity and wages system is just the contract and worthy of Proved the wages workers at maturity can employees the wages welfare. This makes plantation PT Glenmore seek to add the type of jobs with the bulk of the results and in accordance with the requirements and a fair wage and worthy.